Espécies de brássicas no controle de fitopatógenos habitantes do solo - Moccellin, Renata (2011)
The brassicas has high potential biofumigation and they produce toxic gases to volatile soilborne plant pathogens (SPP). This study intend to test three species of brassica: Brassica juncea (mustard), Brassica oleracea (cabbage) and Brassica napus (canola) in the control of three SPP: Sclerotium rolfsii, Rhizoctonia solani and Pythium aphanidermathum. We conducted three tests, the first in vitro, consisting of three treatments: 0, 5, 10, 15, 20 and 25% extract of canola and mustard. Each Petri dish containing culture medium received a disk of PDA containing mycelium of a pathogen. On the cover were placed extracts that were the basis for the board. Readings were taken of mycelial growth. In the second experiment conducted in a greenhouse, we used doses of 0, 30, 60, 90 and 120 t ha-1 cabbage shredded, in two crops. In plastic bags with sealing system were placed 500 g soil and 10 g of substrate with P. Aphanidermathum, then receiving doses of cabbage, with later closing and placing in chamber at 22 ° C for 15 days. Then the soil from each bag was distributed in 16-cell tray seedling cultivation, seeding a cucumber seed per cell. The third and final field test was carried out in two crops, using doses of 0, 30, 60, 90 and 120 t ha-1, canola crushed. In plots of 1m2 is incorporated in a sand and corn containing quirela P. Aphanidermathum and canola crushed after 24 h, with subsequent coverage with double-sided pads. After removing the pads we collected soil samples to assess the survival of the pathogen and for distribution in trays, using the same methodology described in the second test. The survival was performed sowing to five cucumber seeds in plastic cups with sterilized soil, where it was placed 0.5 g of oats and 15 g of soil taken from plots. We have made emergency and tip evaluations. At the plots of the field, we sow 50 seeds of cucumber. For the three experiments were made emergency evaluations, damping off and seedling dry weight. In all soil samples were evaluated microbial activity, soil fertility and electrical conductivity. In the first trial all pathogens reduced the mycelial growth by increasing doses of canola and mustard. In the second and third tests cabbage and canola were effective in all variables. Demonstrated that besides the direct effect on the pathogen through the production of gases, increased microbial activity and electrical conductivity contributed indirectly to control the SPP tested. The concentration of potassium in the soil increased with increasing doses, showing that high levels of potassium in the tissues of crucifers contributed to the control of P. Aphanidermathum, besides serving as an organic fertilizer to places where there is a deficiency of potassium.